Control of alpha-alumina surface charge with carboxylic acids - Bertazzo, Sergio (Langmuir : the ACS journal of surfaces and colloids, 2010)
In this work, we studied the surface charge of alpha-alumina treated with carboxylic acids with different carbon chain length. The results show the possibility of controlling surface charges of alumina by using different concentrations of carboxylic acids or changing the size of the carbon chain of the acids. We also report that part of the acid found on the surface is strongly bound, therefore making it possible to obtain pH-resistant samples of alpha-alumina with an isoelectric point (IEP) of 5.5. It is found, that IEP values obtained for modified samples have a linear correlation with the number of carbon atoms of dicarboxylic acids for up to five carbon atoms. From a practical perspective, the method presented in this work has many advantages. First, it maintains the same hydrophilicity of the alumina surface. Second, the modification of the surface is stable in a long-range of pH. Finally, the presented method is easy-to-use and cheap, as the modification consists of only two simple steps carried out at low temperatures with inexpensive and nontoxic reagents